Piano Sonata no. 1 in F minor, op. 2, no. 1, published by Brandus. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Brandus et Cie.; France; Paris, 2024)
Reprint of the Piano Sonata no. 1 in F minor, op. 2, no. 1, by Brandus & Cie., reprinted from the plates of M. Schlesinger.